2005
DOI: 10.1016/j.engfracmech.2004.03.010
|View full text |Cite
|
Sign up to set email alerts
|

Ductile to brittle transition of an A508 steel characterized by Charpy impact test

Abstract: This study is devoted to the ductile-brittle transition behavior of a French A508 Cl3 (16MND5) steel. Due to its importance for the safety assessment of PWR vessels, a full characterization of this steel with Charpy V-notch test in this range of temperature was undertaken. The aim of this study is to provide a wide experimental database and microstructural observations to supply, calibrate and validate models used in a local approach methodology. Mechanical and fracture properties of the steel have been invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
53
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 165 publications
(54 citation statements)
references
References 57 publications
1
53
0
Order By: Relevance
“…As stated previously the Beremin model is essentially based on the description of the propagation of an existing critical defect belonging to a single population. This is a simplification which might explain why in the application of this model over a wide range of temperatures, a number of investigators have reported that it was necessary to assume the normalizing stress, σ u , to be an increasing function of temperature (see, e.g., Tanguy et al, 2005a, b). This might simply reflect the existence of critical different steps depending on temperature, as indicated earlier.…”
Section: Models Of Cleavage Fracturementioning
confidence: 94%
“…As stated previously the Beremin model is essentially based on the description of the propagation of an existing critical defect belonging to a single population. This is a simplification which might explain why in the application of this model over a wide range of temperatures, a number of investigators have reported that it was necessary to assume the normalizing stress, σ u , to be an increasing function of temperature (see, e.g., Tanguy et al, 2005a, b). This might simply reflect the existence of critical different steps depending on temperature, as indicated earlier.…”
Section: Models Of Cleavage Fracturementioning
confidence: 94%
“…15a show that the predictions are in good agreement with the experiments for Variation of the Charpy energy (CVN) with crack extension from the notch. Experimental results at −60 • C. Calculated probabilities to initiate cleavage fracture (P R = 0.10, 0.50, 0.90) for two temperatures (−60 and −40 • C) (Tanguy et al 2005a, b) temperatures lower than −80 • C. Above this temperature the model largely underestimates the Charpy energy. Similar results have been reported in the literature (Bernauer et al 1999;Rossol et al 2002a, b).…”
Section: Charpy V Notched Impact Tests-modelingmentioning
confidence: 98%
“…However when properly instrumented and numerically modeled this test can also be used as a tool to measure the intrinsic fracture properties of a given steel. This is now briefly illustrated using the results of a study performed on RPV A 508 steel (Tanguy 2001;Tanguy et al 2005a, b).…”
Section: Charpy V Notched Impact Tests-modelingmentioning
confidence: 98%
See 2 more Smart Citations